2014
DOI: 10.1140/epjb/e2014-41025-6
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement switching via the Kondo effect in triple quantum dots

Abstract: Abstract. We consider a triple quantum dot system in a triangular geometry with one of the dots connected to metallic leads. Using Wilson's numerical renormalization group method, we investigate quantum entanglement and its relation to the thermodynamic and transport properties in the regime where each of the dots is singly occupied on average, but with non-negligible charge fluctuations. It is shown that even in the regime of significant charge fluctuations the formation of the Kondo singlets induces switchin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…g , which results in the maximum of the spinup/spin-down conductance in the vicinity of V g = ∓V (3) g . Consequently, the total conductance g(V g ) = g ↑ (V g ) + …”
Section: B Up-down Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…g , which results in the maximum of the spinup/spin-down conductance in the vicinity of V g = ∓V (3) g . Consequently, the total conductance g(V g ) = g ↑ (V g ) + …”
Section: B Up-down Asymmetrymentioning
confidence: 99%
“…Nanostructures based on quantum dots attract growing interest due to an opportunity of tuning of their transport and magnetic properties [1][2][3][4][5][6][7], which makes them promising candidates for quantum spintronics and quantum information processing applications [8][9][10][11][12][13][14][15]. At appropriate conditions, these systems consist of discrete energy levels of quantum dots, which are hybridized with the leads, having continuous energy bands.…”
Section: Introductionmentioning
confidence: 99%
“…This quantum transition was investigated in several theoretical studies as a unique feature of the Kondo effect for a triangular loop of three magnetic impurities. 44,47,48) In the present study, we have focused on the KIEP in the equilateral TTQD, and the result also holds for the lower-symmetry case t bc > t c .…”
Section: Summary and Concluding Remarksmentioning
confidence: 72%
“…In attempt to propose such correlation functions, one need to point out the relevance of quantum fluctuations between electronic doubly-occupied sites and unoccupied sites and between singly occupied sites with spin up and spin down in lattice models, as suggested before by numerous authors [15][16][17][18][19]. The concept quantum entanglement [20,21], together with entanglement measures such as the concurrence [22], was adopted to quantify the above-mentioned fluctuations in various systems [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], including basic spin models [23][24][25]42], fermionic systems [26][27][28][29][30][31], or systems with spin and orbital degrees of freedom [32][33][34][35]. For an open fermionic system (namely: acorrelated quantum dot attached to the leads) we found that the concurrence, defined separately for charge and spin degrees of freedom, allowed one to distinguish between different quantum transport regimes of the system [36].…”
Section: Introductionmentioning
confidence: 99%